2014
DOI: 10.1093/dnares/dsu043
|View full text |Cite
|
Sign up to set email alerts
|

A complete view of the genetic diversity of the Escherichia coli O-antigen biosynthesis gene cluster

Abstract: The O antigen constitutes the outermost part of the lipopolysaccharide layer in Gram-negative bacteria. The chemical composition and structure of the O antigen show high levels of variation even within a single species revealing itself as serological diversity. Here, we present a complete sequence set for the O-antigen biosynthesis gene clusters (O-AGCs) from all 184 recognized Escherichia coli O serogroups. By comparing these sequences, we identified 161 well-defined O-AGCs. Based on the wzx/wzy or wzm/wzt ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
178
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(183 citation statements)
references
References 34 publications
(38 reference statements)
5
178
0
Order By: Relevance
“…Together with the microagglutination tests, these results suggest that the 23 strains form a new sero-variety of E. coli. These results were similar to those from other studies that reported the presence of Shigella antigens in strains of E. coli (Navarro, 2010;Iguchi, 2011;Iguchi, 2015). Recently, Iguchi (2015) reported antigenic relationships between E. coli O38 and S. dysenteriae 8; E. coli O169 and O183 with S. boydii 6 and 10.…”
Section: Discussion:-supporting
confidence: 92%
See 2 more Smart Citations
“…Together with the microagglutination tests, these results suggest that the 23 strains form a new sero-variety of E. coli. These results were similar to those from other studies that reported the presence of Shigella antigens in strains of E. coli (Navarro, 2010;Iguchi, 2011;Iguchi, 2015). Recently, Iguchi (2015) reported antigenic relationships between E. coli O38 and S. dysenteriae 8; E. coli O169 and O183 with S. boydii 6 and 10.…”
Section: Discussion:-supporting
confidence: 92%
“…These results were similar to those from other studies that reported the presence of Shigella antigens in strains of E. coli (Navarro, 2010;Iguchi, 2011;Iguchi, 2015). Recently, Iguchi (2015) reported antigenic relationships between E. coli O38 and S. dysenteriae 8; E. coli O169 and O183 with S. boydii 6 and 10. Although 21 shared O antigens were recognized between E. coli and Shigella (Iguchi, 2015), in the case of S. boydii 18 no antigenic cross-reaction was observed with any other E. coli or Shigella somatic antigen (Liu, 2008).…”
Section: Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…Significant progress has been made in establishing their precise structures and modes of assembly. As an example, there are more than 180 chemically and serotypically distinct glycans, giving rise to LPS O-antigens in Escherichia coli, and the structures, genes, and biosynthetic enzymes have been catalogued (1)(2)(3)(4). Diversity in glycoconjugate structures results from recombination events within genetic loci responsible for the synthesis of polysaccharides to generate a new structure and by acquisition of unlinked genes whose products modify existing structures.…”
mentioning
confidence: 99%
“…It is a freely available web tool that requires little or no expertise in bioinformatics to operate. The database was constructed using complete O and H antigen genes from the NCBI nucleotide collection, a comprehensive set of O antigen genes reported by Iguchi et al (8), and WGS of E. coli reference strains from the WHO Collaborating Centre for E. coli at the Statens Serum Institute, Copenhagen, Denmark. All database genes are compared against the genome of each test strain using the BLAST algorithm, and the output is the predicted O and H serotypes, based on the best-matching genes.…”
mentioning
confidence: 99%